DEVELOPMENT OF LIPID-BASED VESICLES OF TERBINAFINE GEL FOR SKIN DELIVERY BY 32FULL FACTORIAL DESIGN - SARASWATHI, T. S.; ROSHINI, R.; DAMODHARAN, N.; MOTHILAL, M.; JANANI, S. K. (International Journal of Applied Pharmaceutics, 2024)
Objective: Terbinafine is a poorly water-soluble and highly permeable allylamine antifungal (BCS-II) drug. In this study, we looked at the possibility of using ethosomes as vesicular lipid nanocarriers to enhance the transdermal delivery of terbinafine. Methods: Using a 32 full factorial design, the ethosomal formulation with different soya lecithin and cholesterol concentrations was improved and optimized. The influence of independent variables, namely soya lecithin and cholesterol concentration in ethosomes was determined by estimating dependent variable including the particle size, polydispersity index, zeta potential, entrapment efficiency, and in vitro drug release. To improve the residence time of ethosomes on the topical application, the ethosomes were incorporated into the carbopol gel. 1% w/v of Carbopol 934 P gel-embedded Terbinafine ethosomes were used to study medication release and skin interactions. Results: Optimized ratios of soya lecithin and cholestrol was used to prepare vesicles. Formulation had a particle size of 1207.39±2.71 nm, entrapment efficiency of 94.46±0.47%, and in vitro diffusion of 51.27±0.16%. It was found that the growth of fungus Aspergillus niger and Candida albicans were inhibited by Ethosomal Gel. However, ethosomal gel had more inhibitory activity on Apergillus niger compared to positive control. Conclusion: The current study suggests that ethosomal vesicles may improve transdermal dispersion without causing skin irritation. Terbinafine-loaded ethosomes have the potential to be one of the most important transdermal application techniques for the treatment of fungi-related disorders.